Behavior of the digital communities on Twitter during the Mexico 2018 elections - Andrade del Cid, Patricia (2020)
In order to asses the importance of political communication in the Mexican political culture, this paper probes into the behavior of digital communities in Twitter during the 2018 Mexico’s presidential election. Research followed a two staged design. First, a large sample of tweets were collected on a daily basis using the package “rtweet” in the R programming environment. Following that, the collected tweets were filtered, cleaned, and a codebook was designed to analyze their contents. The results show that, out of a sample of 4664 publications, candidate Jose Antonio Meade had the largest number of mentions (47%), followed by Andrés Manuel López Obrador (29%) and Ricardo Anaya (24%). “Common citizens” issued 31% of the tweets analyzed, out of which 20% show links to online news outlets, while journalists and media publications accounted for 40% of the sampled tweets. The authors consider that these results characterize the observed digital communication practices as either transformations or extensions of the offline public sphere.